1990
DOI: 10.1159/000243195
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hyperthermia on Thyroid Structure in the Late Gestation Fetal Lamb

Abstract: This study examined the effect of hyperthermia in late gestation on fetal thyroid structure. Mild heat stress (increase of ewe’s rectal temperature to 40.4°C) caused significant changes of fetal thyroid structure. Intra-follicular colloid area was significantly larger in the heat-stressed group (2,532 ± 181 μm2) compared to a control group where rectal temperature of the ewe was within the normal range (1,660 ± 188 μm2; p < 0.01). Epithelial cell height was significantly reduced (2.5 ± 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2000
2000

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…In their experiment, elevated temperatures were maintained for 16-17 h each day. Adrianakis et al (1990) also found no difference in voluntary food intake between heat-stressed ewes inside a climate chamber with an air temperature of 42-46° C in comparison to non-stressed ewes. The daily water intake of Suffolk sheep with access to tree shade in a Mediterranean climate was 33% (7.5 vs. 11.3 l/head) lower (P < 0.05) than in sheep with no shade (Olivares & Caro, 1998).…”
Section: Discussionmentioning
confidence: 70%
“…In their experiment, elevated temperatures were maintained for 16-17 h each day. Adrianakis et al (1990) also found no difference in voluntary food intake between heat-stressed ewes inside a climate chamber with an air temperature of 42-46° C in comparison to non-stressed ewes. The daily water intake of Suffolk sheep with access to tree shade in a Mediterranean climate was 33% (7.5 vs. 11.3 l/head) lower (P < 0.05) than in sheep with no shade (Olivares & Caro, 1998).…”
Section: Discussionmentioning
confidence: 70%